Double-hit B-cell lymphomas - Aukema, Sietse M.; Siebert, Reiner; Schuuring, Ed; van Imhoff, Gustaaf W.; Kluin-Nelemans, Hanneke C.; Boerma, Evert-Jan; Kluin, Philip M. (Blood, 2011)
In many B-cell lymphomas, chromosomal translocations are biologic and diagnostic hallmarks of disease. An intriguing subset is formed by the so-called double- hit (DH) lymphomas that are defined by a chromosomal breakpoint affecting the MYC/8q24 locus in combination with another recurrent breakpoint, mainly a t(14;18)(q32;q21) involving BCL2. Recently, these lymphomas have received increased attention, which contributed to the introduction of a novel category of lymphomas in the 2008 WHO classification, “B cell lymphoma unclassifiable with features intermediate between DLBCL and BL.” In this review we explore the existing literature for the most recurrent types of DH B-cell lymphomas and the involved genes with their functions, as well as their pathology and clinical aspects including therapy and prognosis. The incidence of aggressive B-cell lymphomas other than Burkitt lymphoma with a MYC breakpoint and in particular a double hit is difficult to assess, because screening by methods like FISH has not been applied on large, unselected series, and the published cytogenetic data may be biased to specific categories of lymphomas. DH lymphomas have been classified heterogeneously but mostly as DLBCL, the majority having a germinal center phenotype and expression of BCL2. Patients with DH lymphomas often present with poor prognostic parameters, including elevated LDH, bone marrow and CNS involvement, and a high IPI score. All studies on larger series of patients suggest a poor prognosis, also if treated with RCHOP or high-intensity treatment modalities. Importantly, this poor outcome cannot be accounted for by the mere presence of a MYC/8q24 breakpoint. Likely, the combination of MYC and BCL2 expression and/or a related high genomic complexity are more important. Compared to these DH lymphomas, BCL6+/MYC+ DH lymphomas are far less common, and in fact most of these cases represent BCL2+/BCL6+/MYC+ triple-hit lymphomas with involvement of BCL2 as well. CCND1+/MYC+ DH lymphomas with involvement of 11q13 may also be relatively frequent, the great majority being classified as aggressive variants of mantle cell lymphoma. This suggests that activation of MYC might be an important progression pathway in mantle cell lymphoma as well. Based on clinical significance and the fact that no other solid diagnostic tools are available to identify DH lymphomas, it seems advisable to test all diffuse large B-cell and related lymphomas for MYC and other breakpoints.